Pastoral Practices, Bedding and Fodder During the Early Neolithic Through Micromorphology at Cova Colomera (Southeastern Pre-Pyrenees, Iberia) - Bergadà M. Mercè (De Gruyter, 2021)
The microstratigraphic study of the Cova Colomera (Sant Esteve de la Sarga, Lleida, Spain) confirms that there are several discontinuous ovicaprid stabling episodes in the Late Cardial Neolithic sequence (c. 5250–4780 cal BC). There are episodes with and without combustion traces. From the burnt episodes, it has been possible to identify bedding and fodder due to their good preservation and abundance in the X-32 sector, specifically the level CE14. The main constituents are grassy remains and to a lesser extent, conifer twigs and needles, beech twigs, and box leaves. These data give an idea about the landscape near the cavity. From the nonburnt episodes, we emphasize the sector W-31, specifically the top of level CE13, in which bedding and fodder appear in a smaller quantity. Its components are also well preserved, with an emphasis on sheep/goat excrements in which it has been possible to identify part of their diet composed of leaves and culms of grasses (Poaceae). From these episodes and their components, we propose that Cova Colomera had different uses as a pen of a small size herd. In some episodes, the herd was more permanent in the cave, and therefore, more waste was generated, so burning was required; and in other episodes, occupation was more sporadic and the burning of waste was not so necessary. In short, Cova Colomera allows us to propose that the study of pastoral activities in caves and rockshelters is more complex than previous studies have shown and that it is necessary to analyze these records with high-resolution techniques to broaden the knowledge of these first livestock communities.